2009
DOI: 10.3748/wjg.15.990
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of omeprazole, lansoprazole, pantoprazole and esomeprazole for symptom relief in patients with reflux esophagitis

Abstract: AIM:To clarify whether there is any difference in the symptom relief in patients with reflux esophagitis following the administration of four Proton pump inhibitors (PPIs). METHODS:Two hundred and seventy-four patients with erosive reflux esophagitis were randomized to receive 8 wk of 20 mg omeprazole (n = 68), 30 mg of lansoprazole (n = 69), 40 mg of pantoprazole (n = 69), 40 mg of esomeprazole (n = 68) once a day in the morning. Daily changes in heartburn and acid reflux symptoms in the first 7 d of administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
4
33
0
2
Order By: Relevance
“…Results of another study (Zheng ), which compared the efficacy of OME, pantoprazole, lansoprazole, and esomeprazole using symptom relief as an endpoint, were consistent with those of a study comparing the effects of the PPIs using intragastric pH as the endpoint (Rohss et al. ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Results of another study (Zheng ), which compared the efficacy of OME, pantoprazole, lansoprazole, and esomeprazole using symptom relief as an endpoint, were consistent with those of a study comparing the effects of the PPIs using intragastric pH as the endpoint (Rohss et al. ).…”
Section: Discussionsupporting
confidence: 68%
“…Both studies concluded that DR‐esomeprazole 40 mg was more effective than DR‐omeprazole 20 mg, DR‐lansoprazole 30 mg, and DR‐pantoprazole 40 mg (Rohss et al. ; Zheng ). Therefore, whether a true relationship exists between relief of clinical symptoms and control of intragastric pH is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, options for prophylaxis include antacids, H2-RAs, sucralfate and PPIs. In order to evaluate the adequacy of dosing these agents, a review of the literature was needed to extract the recommended doses since most of the medications used for SUP are not FDA approved for this indication (Table 2) [9,35,36] . Thus, a prescribed dose was considered correct if it coincides with the extrapolated doses.…”
Section: Data Collectionmentioning
confidence: 99%
“…Penelitian sebelumnya tentang profilaksis SRMD dan penggunaan PPI pada pesien dengan reflux esophagitis menyatakan bahwa jenis kelamin, usia dan lama rawat tidak berbeda signifikan antar kelompok terapi 6,7 . Jumlah faktor risiko yang dimiliki oleh pasien merupakan satusatunya karakteristik pasien yang memiliki perbedaan antar kelompok terapi pantoprazol dan omeprazol (p<0,05).…”
Section: Hasil Penelitian Dan Pembahasan Karakteristik Pasienunclassified
“…Walaupun terdapat perbedaan jumlah pasien pada kedua kelompok terapi, tetapi setelah dilakukan uji statistik dengan Chi Square didapat nilai p=0,512 (P>0,05) yang berarti bahwa tidak terdapat perbedaan efektivitas antara kelompok terapi pantoprazol dengan kelompok terapi omeprazol. Sebuah penelitian menyebutkan bahwa tidak terdapat perbedaan signifikan antara penggunaan omeprazol dan pantoprazol dalam menangani refluks esofagitis selama 4-8 minggu 5,7 .…”
Section: Efektivitasunclassified